Real time multiple planar volume clipping based on the programmable graphics process unit - Yuan, Feiniu (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
We propose a real time volume clipping method which is capable of using several analytical planes for virtual clipping, in order to display internal anatomical structures within volumetric data sets. A single proxy plane is used for computation of the direction of a ray that is cast from the viewpoint. Intersections between the rays and the planes are computed on graphics process unit (GPU). The start and end points for each ray are determined by analyzing relationships with the ray direction, intersections and the normal of planes. Then the volume integral is computed along the ray from the start point to the end point. To obtain immediate visual feedback of clipping effects, we implement translation and rotation of planes on GPU to interactively change the shape of clip object. At last, several experiments were performed on a standard PC with a GeForce FX8600 graphics card. Experimental results show that the method can freely clip and clearly visualize volumetric data sets at real time frame rates.
Optica Applicata, Vol. 39, 2009, nr 2, s. 331-345
Keywords: optyka; planar volume clipping; graphics process unit (GPU) ray casting; single proxy plane